Relationships between Shanghai Five Different Home-Brewed Wines Sensory Properties and Their Volatile Composition Assessed by GC-MS - Xin Dang; Tao Feng; LingYun Yao; Da Chen (Journal of Food Quality)
In order to determine the key aroma components of home-brewed wines made from different local grapes in Shanghai. In the work, the identification and quantification of 63 aroma compounds of five home-brewed wines characterized by gas chromatography-mass spectrometry (GC-MS) combined with Headspace Solid-Phase Microextraction (HS-SPME). To study the possible correlation between the sensory attributions and 22 aroma compounds in Odor Activity Value (OAV) > 1 for five home-brewed wines, the Partial Least Squares Regression (PLSR) was a multivariate data analysis performed. Furthermore, to investigate the percentage of contribution of a particular aroma compound to its overall flavor, the relative odor contribution (ROC) and odor activity value of volatiles in home-brewed wines were conducted and performed. According to the comprehensive results, Summer Black Seedless grape (SBSG) and Black Beet grape (BBG) were the most appropriate varieties to be brewed wines for people in Shanghai or around it.